2016
DOI: 10.1007/s00436-016-4959-8
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation and bioactivity of the essential oils of two Juniperus species against Aedes (Stegomyia) albopictus (Skuse, 1894)

Abstract: The seasonal variation in respect to the yield and chemical composition of 24 essential oils (EOs) isolated from various parts (leaves and fruits) of two indigenous Greece Juniperus species (family Cupressaceae), namely Juniperus drupacea and Juniperus phoenica, were determined by GC and GC/MS analysis. The larvicidal properties of these EOs were evaluated against 3rd and early 4th instar larvae of Aedes (Stegomyia) albopictus (Skuse, 1894) at one screening dose (29 mg L(-1)). Moreover, the repellent activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…In summer, wild juniperus species were reversed for α ‐cedrol. Previous literature also showed that the seasonal and phenological variations greatly affected EOs composition . α ‐Pinene was favored for the exceptional pharmaceutical uses, and due to its pleasant aroma, it is extensively used in perfumery industry, while limonene was found immense applications in formulations of commercially available flea, shampoos, mosquito repellents and diverse agrochemicals .…”
Section: Resultsmentioning
confidence: 99%
“…In summer, wild juniperus species were reversed for α ‐cedrol. Previous literature also showed that the seasonal and phenological variations greatly affected EOs composition . α ‐Pinene was favored for the exceptional pharmaceutical uses, and due to its pleasant aroma, it is extensively used in perfumery industry, while limonene was found immense applications in formulations of commercially available flea, shampoos, mosquito repellents and diverse agrochemicals .…”
Section: Resultsmentioning
confidence: 99%
“…albopictus activity with LC 50 values of 3 and 9 μg/ml, respectively (Akihara et al, 2018). Moreover, diterpenoids of the essential oils of Juniperus drupacea and J. phoenica were found to act against this dengue vector (Evergetis et al, 2016). Listed in Table 3 are diterpenes or diterpenoids that show bioactivity against Ae.…”
Section: Aedes Albopictusmentioning
confidence: 99%
“…All EOs were obtained by hydro-distillation using a modified Clevenger apparatus, according to previously described procedure (Evergetis et al, 2016). In addition the EO from Echinophora tenuifolia ssp.…”
Section: Essential Oils Isolation and Analysesmentioning
confidence: 99%